Negative pressure pulmonary edema in a patient undergoing open rhinoplasty: A case report. Issue 1 (8th January 2021) - Park, Hanwool; Nam, Sugeun; Jang, Yong Ju; Ku, Seungwoo; Choi, Seong-Soo
Abstract: Rationale: Negative pressure pulmonary edema (NPPE) is associated with serious postoperative complications. Compact nasal packing is always done after an open rhinoplasty procedure which makes it difficult to achieve positive pressure ventilation via a mask if NPPE arises. Patient concerns: A 21-year-old healthy man got an open rhinoplasty, septal perforation repair, and revisional septal reconstruction. After surgery, he became so agitated that it was difficult to calm him. We decided to remove the endotracheal tube. On arrival at the post-anesthesia care unit, he was cyanotic and his SpO2 had decreased to about 2%. We attempted positive pressure ventilation using mask bagging; however, it was ineffective due to the nasal packing. Diagnoses: Negative pressure pulmonary edema Interventions: Emergent reintubation was immediately done and Ambu bagging was commenced. A considerable pinkish secretion came out of the tube. A T-piece was applied to him using 15 L/min of oxygen supply. The patient was eventually transferred to the intensive care unit of our hospital. Outcomes: On postoperative day (POD) 1, a decision was made to extubate, and the oxygen supply was shifted to 3L/min using a venturi-mask. On POD 2, a chest posteroanterior radiograph was taken and indicated no active lung lesion. The patient was subsequently discharged without any complications. He had no symptoms on POD 6, 11, and 18 at follow-up visits to our outpatient clinic. Lessons: Anesthesiologists should be alert to the possibility of NPPE and its treatment because of its rapid onset but positive clinical outcome if there is a proper intervention. In nasal surgery cases in particular, early re-intubation should be conducted and extubation should be done to fully awaken the patients.